Feasibility Study of ICE Bottoming ORC with Water/EG Mixture as Working Fluid. (September 2017) - Ziviani, Davide; Kim, Donghun; Subramanian, Swami Nathan; Braun, James E.; Groll, Eckhard A.
Abstract: To achieve the U.S. Department of Energys brake thermal efficiency (BTE) goal for Heavy Duty Diesel Engine (HDDE) technologies, Waste Heat Recovery (WHR) by means of Organic Rankine Cycle (ORC) systems has been selected as a suitable solution. The current relatively high return on investment period of such technology needs to be improved by significant cost reductions to realize benefits on WHR for mobile applications. The performance of the ORC system under dynamic loads relies on the choice of the working fluid, the efficiency of its components (mainly expander) as well as the control strategy that optimizes the operation. A novel ORC architecture is proposed that uses the engine coolant as the working fluid. In particular, a fraction of the engine coolant, which is a mixture of water and ethylene glycol, is employed as working fluid through the ORC to recover waste heat from EGR (Exhaust Gas Recirculation) and part of the tail pipe exhaust gases. At the inlet of the expander, the mixture has mixed-phase conditions and a fixed volume ratio expander is employed to generate power output that can be fed directly to the engine crankshaft. Heat rejection is accomplished through the spare capacity of the engine radiator, which avoids the need for a separate condenser. To evaluate the feasibility of such system architecture, a thermodynamic steady-state cycle model has been developed to predict the potential increase of BTE under different engine loads as well as to understand the ORC performance. Parametric studies are carried out by varying the system pressure ratio, the internal volume ratio of the expander and the mixture quality at the expander inlet.